Body Mass Index is a Predictor of Fire Fighter Injury and Worker Compensation Claims - Kuehl, Kerry S. (2012)
OBJECTIVE: To determine the relationship between lifestyle variables including body mass index (BMI) and filing a worker’s compensation claim due to firefighter injury. METHODS: A cross-sectional evaluation of firefighter injury related worker compensation claims occurring 5 years after the original PHLAME study intervention. RESULTS: Logistic regression analysis for variables predicting filing a worker’s compensation claim due to an injury were performed. with a total of 433 participants. The odds of filing a compensation claim were almost three times higher for firefighters with a BMI >30 compared to firefighters with normal BMI (odds ratio=2.89, p<.05). CONCLUSIONS: This study addresses a high priority area of reducing firefighter injuries and worker’s compensation claims. Maintaining a healthy body weight is important to reduce injury and worker’s compensation claims among firefighters.